Analysis of Adaptive Evolution and Coevolution of rbcL Gene in the Genus Hildenbrandia (Rhodophyta). (December 2020) - Fangru, Nan; Yuxin, Han; Xudong, Liu; Jia, Feng; Junping, Lv; Qi, Liu; Shulian, Xie
The adaptive evolution and coevolution of the ribulose-1, 5-bisphosphate carboxylase/oxygenase large subunit ( rbc L) gene in the genus Hildenbrandia were studied based on phylogenetic tree construction and the physicochemical properties and the secondary structures of protein encoded by rbc L (Rubisco large subunit) were analyzed. The amino acids compositions and grand average of hydropathicity of freshwater H. rivularis and marine H. rubra were similar. Rubisco large subunit of Hildenbrandia was hydrophilic and the secondary structure was primarily composed of α-helixes and β-sheets, revealing the relatively stable structure of this protein. The predicted phosphorylation sites in H. rivularis and H. rubra were 33 and 36, respectively. No positive selection sites were detected in the genus Hildenbrandia, implying that rbc L gene evolved either neutrally or under purifying selection. A total of 41 coevolutionary groups were detected in the Rubisco large subunit of Hildenbrandia and the coevolving sites are in closer proximity in 3-dimensional structure of the protein. Despite the long evolutionary history, rbc L gene in genus Hildenbrandia under different environments is rather conservative.